Simulasi Performa Turbin Propeller Dengan Sudut Pitch Yang Divariasikan - Pribadyo Pribadyo; Hadiyanto H; Jamari J (universitas teuku umar, 2020)
Propeller turbine performance can be improved by changing the turbine design parameters. One method that was developed is to vary the blade angle on the runner's blades. Analysis of the influence of blade angle on propeller turbine performance is done through numerical simulations based on computational fluid dynamics. The simulation is done with variations of propeller turbine blade angles of 180, 230, and 280 at flow rates of 0.08 m/s to 0.5 m/s. Simulation results show turbines with 250 blade angles have the best performance compared to turbine blade angles of 230 and 280. While the turbine blade angles of 230 tend to have higher performance compared to angles of 280 even though both have peak values for the corresponding power coefficient. Keywords—Propeller turbine, runner blade, pitch angle, CFD simulation